Comparative radio‐frequency and crosstalk analysis of carbon‐based nano‐interconnects. Issue 6 (28th February 2021) - Kaur, Manjit; Gupta, Neena; Kumar, Sanjeev; Raj, Balwinder; Singh, Arun K.
Abstract: A comparative radio‐frequency (RF) and crosstalk analysis is performed on carbon nano‐interconnects based on an efficient π ‐type equivalent single‐conductor model of bundled multiwall carbon nanotubes (MWCNTs) and stacked multilayer graphene nanoribbons (MLGNRs). Simulation results are extracted using HSPICE for global‐level nano‐interconnects at the 14‐nm node. RF performance is evaluated in terms of skin depth and a 3‐dB bandwidth, while crosstalk performance is analysed in terms of crosstalk‐induced delay and average power consumption. The skin‐depth results indicate significant improvements in skin‐depth degradation at higher frequencies for AsF5 ‐doped zig‐zag MLGNRs compared with that of Cu, nanotubes and MWCNTs. The transfer gain results explicitly demonstrate that AsF5 ‐doped MLGNRs exhibit excellent RF behaviour, showing 10‐ and 20‐fold improvements over MWCNTs and copper (Cu), respectively. Further, the 3‐dB bandwidth calculations for AsF5 ‐doped MLGNRs suggest 18.6‐ and 9.7‐fold enhancement compared with Cu and MWCNTs at 1000 μm. Significant reductions are obtained in crosstalk‐induced out‐of‐phase delays for AsF5 ‐doped MLGNRs—their delay values were 84.7% and 60.24% less than those for Cu and MWCNTs. Further, AsF5 ‐doped MLGNRs present the most optimal energy‐delay product results, with values representing 98.6% and 99.6% improvements over their Cu and MWCNT counterparts at a global length of 1000 µm.